Manejo del trauma penetrante cervical. Serie de casos y revisión de la literatura - Jans B., Jaime; Bórquez M., Pablo; Marambio G., Andrés; Cruz M., Javier; Villegas V., David; Hollstein G., Alejandro (Revista Hospital Clínico Universidad de Chile, 2011)
Introduction: Penetrating neck trauma is a rare disease, but with high severity that affects the Emergency Room Services. Morbidity and mortality are due to injury of vascular structures and the aerodigestive tract. Conservative or surgical management depends on hemodynamic stability, the affected cervical zone and the presence of clinical signs of alert. Objective: To describe cervical penetrating trauma managed in the emergency unit of the Hospital Base Osorno, between January 2004 and April 2011 and review the literature. Material and Methods: We performed a retrospective review of all patients with penetrating cervical trauma seen at our center in this period. Results: Twelve patients were treated, nine were male. The average age was 29 years, ranging from 4 to 55 years. Zone II was the most affected with 9 cases. Eight were stab injuries. The main surgical indications were active bleeding, subcutaneous emphysema and air exiting from the wound. The average length of hospital stay was 3,9 days. One patient died. Conclusions: In our center, penetrating neck trauma is a rare disease, which usually requires a surgical approach, forcing the emergency surgeon to be aware of warning signs to determine the need for surgical exploration or conservative management.